2010
DOI: 10.1111/j.1743-6109.2010.01849.x
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Dysfunction in the Community: Trends over Time in Incidence, Prevalence, GP Consultation and Medication Use—the Krimpen Study: Trends in ED

Abstract: Introduction In the general population, erectile dysfunction (ED) is surrounded by a “taboo.” Epidemiologists studying this problem have to be aware of the phenomenon of the “tip-of-the-iceberg.” Aims Our aim is to describe the iceberg phenomenon for ED and their help-seeking behavior in the general population during a period when public interest in ED heightened and waned after the introduction of the drug sildenafil. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 29 publications
0
29
1
Order By: Relevance
“…One study found that smoking was significantly negatively associated with help seeking [13]. Another study found that men who contacted the GP regarding ED were slightly but significantly more overweight compared to the men who did not contact a GP [31]. We found no significant associations between smoking status, alcohol consumption, BMI and contact with a GP.…”
Section: Findings In Relation To Other Studiescontrasting
confidence: 67%
“…One study found that smoking was significantly negatively associated with help seeking [13]. Another study found that men who contacted the GP regarding ED were slightly but significantly more overweight compared to the men who did not contact a GP [31]. We found no significant associations between smoking status, alcohol consumption, BMI and contact with a GP.…”
Section: Findings In Relation To Other Studiescontrasting
confidence: 67%
“…The global prevalence of ED, as measured by all other questionnaires, was 3-76.5% (Table 3 [5,19,[37][38][39][40][41][42][43][44][45][46][47][48][49][50]). The prevalence by continent was: 22-46.3% [5,42,46], 14% [5], 10-76.5% [5,37,38,40,45,48,50], 49.4% [47], 8-65% [19,[39][40][41]43,44], 53.6% [49] for North America, South America, Europe, Oceania, Asia and Africa, respectively. The prevalence of ED increased with increasing age [5,19,38,[40][41][42][43][44]50].…”
Section: Ed Prevalencementioning
confidence: 99%
“…ing and procurement (6). For the achievement of successful intercourse, PDE5is that have been prescribed for more than a decade have demonstrated favourable efficacy (7), ranging from 52% to 66% at their highest doses (8)(9)(10).…”
Section: • Efficacy (Successful Intercourse; Sexual Encountermentioning
confidence: 99%
“…Several factors, including clinical presentation, patient demographic and personal situation, may influence the choice of a PDE5i (5), and data from a large longitudinal community‐based study from the Netherlands (the Krimpen study) suggested that the availability and awareness of new treatment options (i.e. PDE5is) for ED induced a change of behaviour in general practitioners and their patients, regarding treatment‐seeking and procurement (6). For the achievement of successful intercourse, PDE5is that have been prescribed for more than a decade have demonstrated favourable efficacy (7), ranging from 52% to 66% at their highest doses (8–10).…”
Section: Introductionmentioning
confidence: 99%